Quantification of the effect of precipitation as a triggering factor for landslides on the surroundings of medellín – colombia (2014)
Malamud et al. [7] presented a theoretical function that explains the relationship between the area of landslides associated to a certain triggering event (heavy rainfall, snow melting, earthquake) and its frequency. This probability density function was applied to a landslides inventory mapped outside the city of Medellín, distinguishing between landslides (in natural slopes) and slope failures (so called man-made slopes). As a result, the statistic behavior of large landslides is very similar to the theoretical curve presented by the authors referred above, while the probability of occurrence of small landslides, those with areas smaller than 5x10-4 km2, is much higher, especially on man-made slope failures. Considering that this behavior is clearly manifested on man-made slope failures, it can be inferred that there is an effect of the road on the increase of the periodicity of the slides and there for, the popular hypothesis of associating road slope failure only to precipitation is questionable.